Sensorimotor cortex plasticity in upper-limb amputees - Kikkert, S (2017)
The current thesis was aimed at investigating how the primary sensorimotor cortex, and in particular the missing hand cortex, is affected by upper-limb amputation. This thesis further explores how activity in this region relates to phantom limb pain (PLP). As such, a series of neuroimaging experiments was designed, aimed at answering 3 main questions: 1) What happens to the neural fingerprint of a hand following its amputation? 2) What are the behavioural and neural underpinnings of PLP? 3) Can novel targets for PLP treatment be identified? By making use of ultra-high field 7 tesla fMRI and the phenomenology of phantom limb sensations, this thesis demonstrates that the topographical representation of a missing hand’s individual digits is preserved in primary somatosensory cortex, even decades after arm amputation. This finding of stable topography questions the extent to which continued sensory input is necessary to maintain organisation in sensory cortex. Slowed phantom hand motor control was identified as a behavioural correlate of chronic PLP. Stronger maintained activity in the primary sensorimotor missing hand cortex was reaffirmed as a neural correlate of chronic PLP and was further associated with deteriorated phantom hand motor control. This thesis presents results challenging the maladaptive plasticity model and instead emphasising a likely relationship between persistent peripheral inputs pertaining to the missing hand representation and chronic PLP. Anodal tDCS over the primary sensorimotor missing cortex during a phantom hand movement task effectively relieved PLP with effects lasting at least one week post stimulation. In accordance with above, amputees with more PLP relief showed less activity in the primary sensorimotor cortex after brain stimulation. Importantly, tDCS-concurrent neuroimaging identified the insula and secondary somatosensory cortex as neural correlates of PLP relief and subsequent sensorimotor cortex downregulation. Together, this thesis reveals new roles of primary sensorimotor cortex following arm amputation and provides a first comprehensive overview of the neural mechanisms underlying missing hand sensations, offering novel opportunities for PLP treatment.